Anxiolytic activity and active principles of Piper amalago (Piperaceae), a medicinal plant used by the Q'eqchi' Maya to treat susto, a culture-bound illness. (5th June 2016) - Mullally, M.; Cayer, C.; Muhammad, A.; Walshe-Roussel, B.; Ahmed, F.; Sanchez-Vindas, P.E.; Otarola Rojas, M.; Merali, Z.; Cal, V.; Durst, T.; Trudeau, V.L.; Arnason, J.T.
Abstract: Ethnopharmacological relevance: The medicinal plant, Piper amalago L. (Piperaceae), is used traditionally by Q'eqchi' Maya healers for the treatment of "susto" a culture-bound syndrome. Previous research suggests that susto symptoms may be a manifestation of anxiety. The objectives were to characterize the effect of ethanolic extract of P. amalago in behavioral assays of anxiety at doses representative of traditional use and to isolate active principles. Materials and methods: Rats treated orally with low dose ethanolic extracts of P. amalago leaves (8–75 mg/kg) were tested in several behavioral paradigms including the elevated plus maze (EPM), social interaction (SI), and conditioned emotional response (CER) tests, and compared to diazepam, a positive control. The active anxiolytic principle was isolated by bioassay guided isolation using an in vitro GABAA competitive binding assay. Results: Extracts had significant anxiolytic activity in all behavioral tests, with the strongest activity in the SI and the CER paradigms. In an in vitro GABAA competitive binding assay, a 66.5 µg/mL concentration of P. amalago ethanol extract displaced 50% of the GABAA –BZD receptor ligand [ 3 H]-Flunitrazepam. Bioassay-guided fractionation identified a furofuran lignan, a molecule with structural similarity to yangambin, with high affinity for the GABAA -BZD receptor as the principle bioactive. Conclusion: The results suggest that the ethnobotanical use of this plant may have a pharmacological basis in its anxiolytic activity, as demonstrated in animal behaviour tests Graphical abstract: Piper amalago, a plant traditionally used by Q'eqchi' Maya healers for the culture bound syndrome, susto, has significant anxiolytic effects mediated by a furofuran active principle.